"The Light at the End of the Tunnel Has Been Permanently Shut Off": Work-Role Overload Among U.S. Police. (July 2022) - Hofer, Meret S.
The functional breadth of the police role is a primary issue facing law enforcement. However, few empirical data examine how officers are experiencing an occupational environment characterized by an increasingly wider range of new (but routine) duties. I take a qualitative approach to explore experiences of work-role overload via in-depth, semi-structured interviews with a sample of U.S. police officers ( N = 48). By applying the framework for thematic analysis, I find that work-role overload is a robust feature of police officers' occupational experiences and presents in two ways: (a) through quantitative overload related to the excessive volume of work demands and (b) qualitative overload related to strained or diminished psychological resources. The findings provide valuable insights for improving the theoretical understanding of work-role overload among police in light of international trends toward broadening law enforcement's social functions and add to contemporary discussions to "defund the police."